P3HT Molecular Weight Determines the Performance of P3HT:O‐IDTBR Solar Cells. Issue 8 (17th May 2019) - Khan, Jafar Iqbal; Ashraf, Raja Shahid; Alamoudi, Maha A.; Nabi, Mohammed N.; Mohammed, Hamza N.; Wadsworth, Andrew; Firdaus, Yuliar; Zhang, Weimin; Anthopoulos, Thomas D.; McCulloch, Iain; Laquai, Frédéric
Abstract : Large‐scale production of organic solar modules requires low‐cost and reliable materials with reproducible batch‐to‐batch properties. In case of polymers, their (photo)physical properties depend strongly on the polymers' molecular weight (MW). Herein, the impact of the MW of the donor polymer poly(3‐hexylthiophene) (P3HT) on the photophysics is studied in blends with a recently developed rhodanine‐endcapped indacenodithiophene nonfullerene acceptor (IDTBR), a bulk heterojunction (BHJ) system that potentially fulfills the aforementioned criteria for large‐scale production. It is found that the power conversion efficiency (PCE) increases when the weight‐average MW is increased from 17 kDa (PCE: 4.0%) to 34 kDa (PCE: 6.6%), whereas a further increase in MW leads to a reduced PCE of 4.4%. It is demonstrated that the charge generation efficiency, as estimated from time‐delayed collection field experiments, varies with the P3HT MW and is the reason for the differences in photocurrent and device performance. These findings provide insight into the fundamental photophysical reasons of the MW dependence of the PCE, which is taken into account when using polymer‐based nonfullerene acceptor blends in solar cell devices and modules. Abstract : The power conversion efficiency of poly(3‐hexylthiophene) P3HT:O‐IDTBR bulk heterojunction solar cells peaks at intermediate (34 kDa) polymer molecular weights (MWs). Combined transient absorption and time‐delayed collection field experiments demonstrate that charges are generated more efficiently at intermediate P3HT MWs compared with high and low MWs.